PODMIOTOWOŚĆ PRAWNOMIĘDZYNARODOWA JEDNOSTKI - Drobnik, Marcin (Wydział Prawa i Administracji UAM, 2003)
The basic bearer of rights in the international law has traditionally been the state, and the state’s supreme function has been to regulate relations with other states. This is visible in the principle of sovereign equality between states governing international law. The classic law does not directly apply to individuals. In certain respects it refers to the category of the individual, but always by means of norms referring to state or international relations. Norms focusing directly on the individual have only recently started to develop. Traditionally, international law has referred to natural persons only through the state, either through the very notion of state or by referring to relations between states. Classic international law is therefore interested in the individual only as a citizen or foreigner and only insofar as this reference is necessary to define relations between the basic bearers of rights, i.e. when a citizen’s or foreigner’s status significantly influences the determination of the states’ rights and obligations in their mutual relations. Another view is visible in regulations relating to military conflicts. In this area the interest of the state in the individual is determined by the state’s position taken in reference to the given conflict, i.e. whether this is an internal or international conflict. The legal system divides the population participating in the conflict into various categories of individuals with clearly differing legal status.
INDIVIDUAL’S ABILITY TO BEAR RIGHTS IN THE INTERNATIONAL LAW